Epidemiology of cancer in Saudi Arabia thru 2010-2019: a systematic review with constrained meta-analysis Running title: epidemiology of cancer in Saudi Arabia thru 2010-2019 - Wedad Saeed Alqahtani; Nawaf Abdulrahman Almufareh; Dalia Mostafa Domiaty; Gadah Albasher; Manal Abduallah Alduwish; Huda Alkhalaf; Bader Almuzzaini; Salma Sanhaat AL-marshidy; Rgya Alfraihi; Abdelbaset Mohamed Elasbali; Hussain Gadelkarim Ahmed; Bassam Ahmed Almutlaq (AIMS Press, 2020)
Background: Cancer is emerging as a major global health-care system challenge with a growing burden worldwide. Due to the inconsistent cancer registry system in Saudi Arabia, the epidemiology of cancer is still dispersed in the country. Consequently, this review aimed to assemble the epidemiological metrics of cancer in Saudi Arabia in light of the available published data during the period from (2010-2019). Methods: Published literature from Saudi Arabia relating to cancer incidence, prevalence, risk factors, and other epidemiological metrics were accessed through electronic search in Medline/PubMed, Cochrane, Scopus, Web of Knowledge, Google Scholar, and public database that meet the inclusion criteria. Relevant keywords were used during the electronic search about different types of cancers in Saudi Arabia. No filters were used during the electronic searches. Data were pooled and odds ratios (ORs) and 95% confidence interval (95%CI) were calculated. A random-effects meta-analysis was performed to assess the well-determined risk factors associated with different types of cancers. Results: The most common cancers in Saudi Arabia are breast, colorectal, prostate, brain, lymphoma, kidney and thyroid outnumbering respectively. Their prevalence rates and OR (95%CI) as follow: breast cancer 53% and 0.93 (0.84-1.00); colon-rectal cancer (CRC) 50.9% and 1.2 (0.81-1.77); prostate cancer 42.6% and 3.2 (0.88-31.11); brain/Central Nervous System cancer 9.6% and 2.3 (0.01-4.2); Hodgkin and non-Hodgkin's lymphoma 9.2% and 3.02 (1.48-6.17); kidney cancer 4.6% and 2.05 (1.61-2.61), and thyroid cancer 12.9% and 6.77 (2.34-19.53). Conclusion: Within the diverse cancers reported from Saudi Arabia, the epidemiology of some cancers magnitude 3-fold in the latest years. This increase might be attributed to the changing in the Saudi population lifestyle (adopting western model), lack of cancer awareness, lack of screening & early detection programs, social barriers toward cancer investigations. Obesity, genetics, sedentary lifestyle, tobacco use, viral infection, and iodine & Vit-D deficiency represent the apparent cancer risk factors in Saudi Arabia.